Management Student Thinking Process in Solving Functional Problems - Ridho Elvierayani, Rivatul; Emalia Nove Sustyorini; Rachma Dwi Arifani (SEAN Institute, 2022)
Students in solving problems have different abilities according to their intelligence. The purpose of this study was to analyze the thinking processes of management students in solving functional problems. This study used a descriptive qualitative research type. The research subjects consisted of three students with the lowest, medium and highest average learning outcomes. The data collection technique was carried out by triangulation (combined) and the results of qualitative research emphasized meaning rather than generalization. The results show that: (1) Students with high average learning outcomes understand the problem, develop a resolution plan, solve the problem according to the plan and re-examine the results obtained so that the assimilation process is carried out at each stage. (2) Students with average learning are not understanding the problem carefully, causing errors in planning and problem solving. In the re-examination stage, the assimilation and accommodation process is carried out by students. (3) Students with low learning averages make imperfections in the assimilation and accommodation processes both in understanding the problem, compiling a settlement plan, solving problems and re-examining the results obtained.